(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Karnataka needs to develop a cogent policy, strategy oran action plan on inclusive education of children with special needs that canaddress the state specific needs and realities with a long-term vision. Thus,there is a need to put together a statepolicy, strategy and action plan for the education of children with special needs, define the roles and functionsof various departments functionaries pertaining to thisissue and also identify areas where state capacities need to be strengthened in order to meet the challengesof education for children with special needs. In this context, state policy on inclusive education forthe benefit of children with special needs has been developed under thechairmanship of commissioner for public instruction as per the guidelines givenby the secretary for primary and secondary, Govt. of Karnataka.